Calcifying pseudoneoplasm of the spine: imaging and pathological features. Issue 4 (August 2018) - Saha, Atin; Arevalo-Perez, Julio; Peck, Kyung K; Rosenblum, Marc; Bilsky, Mark; Lis, Eric; Karimi, Sasan
Calcifying pseudoneoplasms of the neuraxis are extremely rare calcified lesions that can occur anywhere in the central nervous system. These non-neoplastic lesions have been reported to arise both in the brain and spine with similar frequency and can be found intra-axially as well as extra-axially. The associated symptoms are generally due to mass effect rather than local invasion as calcifying pseudoneoplasms of the neuraxis are usually considered to be benign non-infiltrative lesions. We report a unique case of a 67-year-old male patient who developed lower extremity weakness and gait instability with imaging and histological features of calcifying pseudoneoplasm of the neuraxis occurring in the spine with adhesive features and intradural extension. Calcifying pseudoneoplasms are benign, slow-growing masses that can present with a wide variety of symptoms depending on the size and location of the tumor. The differential diagnosis for these entities can be narrowed taking into consideration relevant imaging features as well as important clinical information.